Preparation process of p-aminophenetole

By catalyzing the reaction between p-aminophenol and ethanol by using an iron-type, supported by a ZSM-22 molecular sieve-supported copper-type composite catalyst, the problem of by-product treatment difficulties and equipment corrosion in the existing process is solved, and efficient and clean preparation of p-aminophenylether is achieved.

CN119793542APending Publication Date: 2025-04-11WANHUA CHEM GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510001844.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-02
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing process of reacting p-aminophenol with ethanol to prepare p-aminophenethyl ether has problems such as difficulty in processing by-products, serious equipment corrosion, high toxicity and high unit price.

Method used

Using an iron-type composite catalyst supported by alumina-vana-carbide MAX-phase ceramic material and a copper-type composite catalyst supported by ZSM-22 molecular sieve, the reaction of p-aminophenol and ethanol was catalyzed through a fixed bed process to form p-aminophenyl ether.

Benefits of technology

It has achieved efficient preparation of p-aminophenylether, with a conversion rate of up to 46%, a selectivity of more than 97%, a cleaner process, no corrosive problems, and a low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005225518650000031
    Figure BDA0005225518650000031
  • Figure BDA0005225518650000061
    Figure BDA0005225518650000061
  • Figure BDA0005225518650000071
    Figure BDA0005225518650000071
Patent Text Reader

Abstract

The invention discloses a synthesis method of p-aminophenetole, which comprises the following step: under the action of a catalyst, catalyzing p-aminophenol and ethanol to generate p-aminophenetole. Wherein the catalyst is a composite catalyst of an iron type supported by a vanadium aluminum carbide MAX phase ceramic material and a copper type supported by a ZSM-22 molecular sieve. The conversion rate of p-aminophenol is more than 46%, the selectivity of p-aminophenyl ether is more than 97%, and continuous and stable operation for more than 3000h can be realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of chemical synthesis, and in particular to a preparation process for preparing p-aminophenethyl ether by reacting p-aminophenol with ethanol. Background Art

[0002] p-Aminophenethyl ether, also known as 4-aminophenethyl ether, 4-ethoxyaniline, p-ethoxyaniline, is an organic compound with the chemical formula C 8 H 11 NO is mainly used as a redox indicator. Currently, it is commonly obtained by reacting p-aminophenol with an ethylating agent in industry. The ethylating agents include diethyl carbonate, diethyl sulfate, ethyl iodide, and ethyl bromide. The byproducts of this method are difficult to handle, and the equipment is severely corroded, highly toxic, and relatively expensive. How to find a cleaner, cheaper, and safer reaction system is an urgent problem to be solved. Summary of the invention

[0003] The purpose of the present invention is to provide a preparation process of p-aminophenethyl ether, which adopts a new catalyst to catalyze p-aminophenol and ethanol to generate p-aminophenethyl ether. Compared with the ethyl bromide and ethyl iodide routes, ethanol is cheaper and safer, the reaction only produces water as a byproduct, the production process is cleaner, and there is no corrosion problem. The technical solution adopted by the present invention is as follows:

[0004] On the one hand, the present invention provides a preparation process of p-aminophenol, comprising the following steps: under the action of a catalyst, p-aminophenol reacts with ethanol to generate p-aminophenyl ether, wherein the catalyst is a composite catalyst in which an iron type supported by an aluminum carbide vanadium MAX phase ceramic material and a copper type supported by a ZSM-22 molecular sieve are mixed in a certain proportion.

[0005] In a preferred embodiment, the catalytic reaction of p-aminophenol and ethanol is carried out in a fixed bed; preferably, the amount of p-aminophenol added is 15-55% of the total mass of p-aminophenol and ethanol.

[0006] In a preferred embodiment, the reaction temperature of p-aminophenol and ethanol is 220-340° C., and the reaction pressure is 2-8 bar(G).

[0007] In a preferred embodiment, the liquid hourly mass space velocity of p-aminophenol is 0.2-0.8h -1 .

[0008] In a specific embodiment, the preparation method of the iron-type composite catalyst supported by aluminum carbide vanadium MAX phase ceramic material and the copper-type composite catalyst supported by ZSM-22 molecular sieve comprises the following steps:

[0009] (1) adding aluminum carbide vanadium MAX phase ceramic material to the iron source aqueous solution and stirring evenly;

[0010] (2) adjusting the pH of the solution in step (1) to a target value, and then drying and calcining to obtain an iron-type catalyst supported by an aluminum-vanadium carbide MAX phase ceramic material;

[0011] (3) adding ZSM-22 molecular sieve to the copper source aqueous solution and stirring evenly;

[0012] (4) adjusting the pH of the solution in step (3) to a target value, and then drying and calcining to obtain a ZSM-22 molecular sieve-supported copper-type catalyst;

[0013] (5) The iron-type catalyst supported by the aluminum vanadium carbide MAX phase ceramic material prepared in step (2) and the copper-type catalyst supported by the ZSM-22 molecular sieve prepared in step (4) are mixed in a certain proportion to obtain a composite catalyst.

[0014] In a specific embodiment, in step (1), the iron source includes one or more of anhydrous ferric chloride, ferric acetylacetonate, ferric fluoride or ferric nitrate nonahydrate, and the mass of water is 15-27 times the mass of the iron source; preferably, the amount of aluminum vanadium carbide MAX phase ceramic material added is 10-50 times the mass of the iron source.

[0015] In a specific embodiment, in step (1), the particle size of the aluminum vanadium carbide MAX phase ceramic material is 5-50 μm.

[0016] In a specific embodiment, in step (2), ammonia water is added to adjust the pH value to 5-7; preferably, the drying temperature is 110-120°C, and the drying time is 6-20h; more preferably, the calcination is carried out in an air atmosphere, the calcination temperature is 450-650°C, and the calcination time is 5-15h.

[0017] In a specific embodiment, in step (3), the copper source includes one or more of anhydrous cupric chloride, cuprous iodide, copper acetylacetonate and copper nitrate trihydrate; the mass of water is 5-20 times the mass of the copper source; preferably, the amount of ZSM-22 molecular sieve added is 10-50 times the amount of the copper source.

[0018] In a specific embodiment, in step (4), ammonia water is added to adjust the pH to 8.1-9.5; preferably, the drying temperature is 110-130°C, and the drying time is 10-30 hours; more preferably, the calcination is carried out in an air atmosphere, the calcination temperature is 400-650°C, and the calcination time is 5-15 hours.

[0019] In a specific embodiment, in step (5), the mass of the iron-type catalyst supported by the aluminum-vanadium carbide MAX phase ceramic material is 0.4-1.6 times the mass of the copper-type catalyst supported by the ZSM-22 molecular sieve.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The method of the present invention provides a method for utilizing p-aminophenol and also provides a novel synthesis process of p-aminophenethyl ether.

[0022] 2) The method of the present invention develops an efficient composite catalyst, uses a continuous fixed bed process, the conversion rate of p-aminophenol is as high as 46%, the selectivity of p-aminophenyl ether is more than 97%, and can be continuously and stably operated for more than 3000 hours. DETAILED DESCRIPTION

[0023] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.

[0024] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which the invention belongs. The term "and / or" as may be used herein includes any and all combinations of one or more of the associated listed items.

[0025] Main raw material sources

[0026]

[0027]

[0028] Main test methods

[0029] Gas chromatography: The composition of the p-aminophenol-ethanol reaction solution was analyzed by gas chromatography. The operating conditions were: Shimadzu GC-2030 gas chromatograph, DB-5MS UI (20m×0.25mm×0.25μm) chromatographic column, N,N-dimethylformamide as diluent. The vaporization chamber temperature was 300°C, the column flow rate was 1.00mL / min, and the injection volume was 0.3μL. The chromatographic column was programmed to heat: first, the temperature was increased from 40°C to 100°C at a heating rate of 2°C / min, and finally, the temperature was increased to 300°C at a heating rate of 10°C / min.

[0030] Reactor used in the embodiment: The reaction adopts a stainless steel fixed bed reactor, the inner diameter of the reaction tube is 19 mm, and Φ3 mmθ rings are filled at both ends of the catalyst.

[0031] Example 1

[0032] The preparation method of the catalyst is as follows:

[0033] (1) Dissolve 10 g of ferric acetylacetonate in pure water, where the mass of the water is 17 times the mass of the ferric acetylacetonate.

[0034] (2) adding aluminum vanadium carbide MAX phase ceramic material to the above solution, wherein the amount of aluminum vanadium carbide MAX phase ceramic material (particle size 24 μm) added is 35 times the mass of iron acetylacetonate, and stirring evenly;

[0035] (3) adding 28% ammonia water to the solution of step (2) to adjust the pH to 5.4;

[0036] (4) drying the solution of step (3) at 120° C. for 10 h;

[0037] (5) calcining the dried sample in step (4) under air atmosphere at 460° C. for 8 h to obtain an iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material;

[0038] (6) Dissolve 10 g of anhydrous copper chloride in pure water, the mass of water being 18 times that of anhydrous copper chloride;

[0039] (7) adding ZSM-22 molecular sieve to the solution of step (6), wherein the amount of ZSM-22 molecular sieve added is 15 times the mass of anhydrous cupric chloride, and stirring evenly;

[0040] (8) adding 28% by mass of aqueous ammonia to the solution of step (7) to adjust the pH to 8.3;

[0041] (9) drying the solution in step (8) at 120° C. for 16 h;

[0042] (10) The sample dried in step (9) was calcined in an air atmosphere at 430° C. for 10 h to obtain a ZSM-22 molecular sieve-supported copper-type catalyst.

[0043] (11) The iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material and the copper-type catalyst supported by ZSM-22 molecular sieve are mixed in a mass ratio of 1.5:1 to obtain the final composite catalyst.

[0044] The reaction conditions of p-aminophenol and ethanol are as follows:

[0045] The reaction of p-aminophenol with ethanol adopts a continuous fixed bed process. The amount of p-aminophenol added is 29% of the total mass of p-aminophenol and ethanol, the reaction temperature of p-aminophenol and ethanol is 250°C, the reaction pressure is 2 bar(G), and the liquid hourly mass space velocity of p-aminophenol is 0.3h -1 .

[0046] After the reaction is stable, samples are taken and the results are analyzed by gas chromatography. The specific results of Example 1 are shown in Table 1.

[0047] Example 2

[0048] The preparation method of the catalyst is as follows:

[0049] (1) Dissolve 10 g of anhydrous ferric chloride in pure water. The mass of water is 21 times the mass of anhydrous ferric chloride.

[0050] (2) adding aluminum vanadium carbide MAX phase ceramic material to the above solution, wherein the amount of aluminum vanadium carbide MAX phase ceramic material (particle size 12 μm) added is 47 times the mass of anhydrous ferric chloride, and stirring evenly;

[0051] (3) adding 28% by mass aqueous ammonia to the solution of step (2) to adjust the pH to 6.8;

[0052] (4) drying the solution of step (3) at 110° C. for 15 h;

[0053] (5) calcining the dried sample in step (4) under air atmosphere at 590° C. for 13 h to obtain an iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material;

[0054] (6) Dissolve 10 g of cuprous iodide in pure water, where the mass of water is 7 times that of cuprous iodide;

[0055] (7) adding ZSM-22 molecular sieve to the solution of step (6), wherein the amount of ZSM-22 molecular sieve added is 35 times the mass of cuprous iodide, and stirring evenly;

[0056] (8) adding 28% by mass of aqueous ammonia to the solution of step (7) to adjust the pH to 8.9;

[0057] (9) drying the solution in step (8) at 130° C. for 12 h;

[0058] (10) The sample dried in step (9) was calcined in an air atmosphere at 590° C. for 12 h to obtain a ZSM-22 molecular sieve-supported copper-type catalyst.

[0059] (11) The iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material and the copper-type catalyst supported by ZSM-22 molecular sieve were mixed in a mass ratio of 0.9:1 to obtain the final composite catalyst.

[0060] The reaction conditions of p-aminophenol and ethanol are as follows:

[0061] The reaction of p-aminophenol and ethanol adopts a continuous fixed bed process, the amount of p-aminophenol added is 49% of the total mass of p-aminophenol and ethanol, the reaction temperature of p-aminophenol and ethanol is 320°C, the reaction pressure is 6 bar(G), and the liquid hourly mass space velocity of p-aminophenol is 0.7h -1 .

[0062] After the reaction is stable, samples are taken and the results are analyzed by gas chromatography. The specific results of Example 2 are shown in Table 1.

[0063] Example 3

[0064] The preparation method of the catalyst is as follows:

[0065] (1) Dissolve 10 g of ferric fluoride in pure water. The mass of the water is 24 times the mass of the ferric fluoride.

[0066] (2) adding aluminum vanadium carbide MAX phase ceramic material to the above solution, wherein the amount of aluminum vanadium carbide MAX phase ceramic material (particle size 31 μm) added is 29 times the mass of ferrous fluoride, and stirring evenly;

[0067] (3) adding 28% by mass aqueous ammonia to the solution of step (2) to adjust the pH to 6.4;

[0068] (4) drying the solution of step (3) at 110° C. for 20 h;

[0069] (5) calcining the sample dried in step (4) in an air atmosphere at 640° C. for 9 h to obtain an iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material;

[0070] (6) Dissolve 10 g of copper acetylacetonate in pure water, where the mass of the water is 15 times that of the copper acetylacetonate;

[0071] (7) adding ZSM-22 molecular sieve to the solution of step (6), wherein the amount of ZSM-22 molecular sieve added is 48 times the mass of copper acetylacetonate, and stirring evenly;

[0072] (8) adding 28% by mass of aqueous ammonia to the solution of step (7) to adjust the pH to 9.1;

[0073] (9) drying the solution in step (8) at 110° C. for 28 h;

[0074] (10) The sample dried in step (9) was calcined in an air atmosphere at 630° C. for 14 h to obtain a ZSM-22 molecular sieve-supported copper-type catalyst.

[0075] (11) The iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material and the copper-type catalyst supported by ZSM-22 molecular sieve are mixed in a mass ratio of 1.1:1 to obtain the final composite catalyst.

[0076] The reaction conditions of p-aminophenol and ethanol are as follows:

[0077] The reaction of p-aminophenol and ethanol adopts a continuous fixed bed process. The amount of p-aminophenol added is 35% of the total mass of p-aminophenol and ethanol. The reaction temperature of p-aminophenol and ethanol is 280°C, the reaction pressure is 3 bar(G), and the liquid hourly mass space velocity of p-aminophenol is 0.5 h -1 .

[0078] After the reaction is stable, samples are taken and the results are analyzed by gas chromatography. The specific results of Example 3 are shown in Table 1.

[0079] Example 4

[0080] The preparation method of the catalyst is as follows:

[0081] (1) Dissolve 10 g of ferric nitrate nonahydrate in pure water, the mass of the water being 19 times the mass of the ferric nitrate nonahydrate.

[0082] (2) adding aluminum vanadium carbide MAX phase ceramic material to the above solution, wherein the amount of aluminum vanadium carbide MAX phase ceramic material (particle size 42 μm) added is 16 times the mass of iron nitrate nonahydrate, and stirring evenly;

[0083] (3) adding 28% ammonia water to the solution of step (2) to adjust the pH to 6.1;

[0084] (4) drying the solution of step (3) at 120° C. for 8 h;

[0085] (5) calcining the dried sample in step (4) under air atmosphere at 510° C. for 11 h to obtain an iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material;

[0086] (6) Dissolve 10 g of copper nitrate trihydrate in pure water, where the mass of water is 11 times that of copper nitrate hydrate;

[0087] (7) adding ZSM-22 molecular sieve to the solution of step (6), wherein the amount of ZSM-22 molecular sieve added is 24 times the mass of copper nitrate trihydrate, and stirring evenly;

[0088] (8) adding 28% by mass of aqueous ammonia to the solution of step (7) to adjust the pH to 9.4;

[0089] (9) drying the solution in step (8) at 120° C. for 23 h;

[0090] (10) The sample dried in step (9) was calcined in an air atmosphere at 500° C. for 6 h to obtain a ZSM-22 molecular sieve-supported copper-type catalyst.

[0091] (11) The iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material and the copper-type catalyst supported by ZSM-22 molecular sieve are mixed in a mass ratio of 0.7:1 to obtain the final composite catalyst.

[0092] The reaction conditions of p-aminophenol and ethanol are as follows:

[0093] The reaction of p-aminophenol with ethanol adopts a continuous fixed bed process. The amount of p-aminophenol added is 18% of the total mass of p-aminophenol and ethanol, the reaction temperature of p-aminophenol and ethanol is 230°C, the reaction pressure is 5 bar(G), and the liquid hourly mass space velocity of p-aminophenol is 0.4h -1 .

[0094] After the reaction stabilized, samples were taken and analyzed using gas chromatography. The specific results of Example 4 are shown in Table 1.

[0095] Comparative Example 1

[0096] The difference from Example 2 is that the catalyst only uses an iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material.

[0097] Comparative Example 2

[0098] The difference from Example 2 is that the catalyst used is only a copper-type catalyst supported by ZSM-22 molecular sieve.

[0099] The catalyst prepared in Example 2 was used for life test. The specific reaction steps were the same as those in Example 2. After running for 3000 hours, the conversion rate was 46.4% and the selectivity was 97%. The activity and selectivity did not decrease significantly.

[0100] Table 1 Conversion rate and selectivity of each example

[0101]

[0102]

[0103] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.

Claims

1. A method for preparing an iron-type composite catalyst supported by aluminum carbide vanadium MAX phase ceramic material and a copper-type composite catalyst supported by ZSM-22 molecular sieve, characterized in that: The steps include: (1) adding aluminum carbide vanadium MAX phase ceramic material to the iron source aqueous solution and stirring evenly; (2) adjusting the pH of the solution in step (1), and then drying and calcining to obtain an iron-type catalyst supported by aluminum carbide vanadium MAX phase ceramic material; (3) adding ZSM-22 molecular sieve to the copper source aqueous solution and stirring evenly; (4) adjusting the pH of the solution in step (3), and then drying and calcining to obtain a ZSM-22 molecular sieve-supported copper-type catalyst; (5) The iron-type catalyst supported by the aluminum vanadium carbide MAX phase ceramic material prepared in step (2) and the copper-type catalyst supported by the ZSM-22 molecular sieve prepared in step (4) are mixed to obtain a composite catalyst.

2. The method according to claim 1, characterized in that In the step (1), the iron source includes one or more of anhydrous ferric chloride, ferric acetylacetonate, ferric fluoride or ferric nitrate nonahydrate, and the mass of water is 15-27 times the mass of the iron source; Preferably, the particle size of the aluminum vanadium carbide MAX phase ceramic material is 5-50 μm; and the added amount of the aluminum vanadium carbide MAX phase ceramic material is 10-50 times the mass of the iron source.

3. The method according to claim 1, characterized in that In the step (2), adding ammonia water to adjust the pH value to 5-7; Preferably, the drying temperature is 110-120°C and the drying time is 6-20h; Preferably, the calcination is carried out in an air atmosphere, the calcination temperature is 450-650° C., and the calcination time is 5-15 h.

4. The method according to claim 1, characterized in that In the step (3), the copper source includes one or more of anhydrous cupric chloride, cuprous iodide, copper acetylacetonate and cupric nitrate hydrate; the mass of water is 5-20 times the mass of the copper source; Preferably, the added amount of ZSM-22 molecular sieve is 10-50 times that of the copper source.

5. The method according to claim 1, characterized in that In the step (4), adding aqueous ammonia to adjust the pH to 8.1-9.5; Preferably, the drying temperature is 110-130°C and the drying time is 10-30h; Preferably, the calcination is carried out in an air atmosphere, the calcination temperature is 400-650° C., and the calcination time is 5-15 hours.

6. The method according to claim 1, characterized in that In the step (5), the mass of the iron-type catalyst supported by the aluminum vanadium carbide MAX phase ceramic material is 0.4-1.6 times the mass of the copper-type catalyst supported by the ZSM-22 molecular sieve.

7. A process for preparing p-aminophenyl ether, characterized in that: Under the action of a catalyst, p-aminophenol and ethanol are reacted to generate p-aminophenethyl ether, wherein the catalyst is a composite catalyst prepared by the preparation method according to any one of claims 1 to 6.

8. The method according to claim 7, characterized in that The added amount of p-aminophenol is 15-55% of the total mass of p-aminophenol and ethanol.

9. The method according to claim 7, characterized in that: The reaction temperature of p-aminophenol and ethanol is 220-340° C., and the reaction pressure is 2-8 bar(G).

10. The method according to any one of claims 7 to 9, characterized in that: The liquid mass space velocity of p-aminophenol is 0.2-0.8h -1 .